Evaluating for health equity among a cluster of health departments implementing PrEP services. (February 2022) - Carter, Jarvis W.; Salabarría-Peña, Yamir; Fields, Errol L.; Robinson, William T.
Highlights: Evaluating health equity strategies can help reduce HIV-related disparities. Engaging priority populations is critical when evaluating health equity strategies. Routinize evaluation of health equity activities to improve HIV-related outcomes. Review, evaluate, and modify organizational policies to improve health equity. Utilize participatory evaluations with key stakeholders to achieve health equity. Abstract: African American/Black and Hispanic/Latino sexual and gender minority populations are disproportionately affected by HIV in the United States and continue to experience HIV-related disparities. CDC funded project PrIDE to support 12 health departments (HD) with implementing pre-exposure prophylaxis (PrEP) strategies for men who have sex with men (MSM) and transgender persons, with a health-equity focus established by HDs. Each HD conducted mixed-methods evaluation of at least one local strategy. CDC employed a cluster evaluation approach to maximize cross validation. As a result, this cluster evaluation focused on three HDs that evaluated health equity-focused PrEP implementation strategies. Findings suggest that integrating health equity strategies such as storytelling and healthcare worker (HCW) trainings can help reduce HIV-related disparities. Storytelling improved HCW's understanding of clients' experiences of stigma due to racial, gender, and sexual identities. Provider training increased competencies on culturally appropriate care and the use of clinic services by Black and Hispanic MSM and transgender persons. Good practices included community engagement, seeking leadership buy-in, and integration of programmatic staff in health equity and evaluation activities. Evaluating strategies and training policies addressing social determinants of health that adversely affect HIV outcomes may help mitigate barriers Black and Hispanic MSM and transgender populations encounter in their HIV prevention seeking efforts.